2016
DOI: 10.1038/srep27504
|View full text |Cite
|
Sign up to set email alerts
|

Responses of corn physiology and yield to six agricultural practices over three years in middle Tennessee

Abstract: Different agricultural practices may have substantial impacts on crop physiology and yield. However, it is still not entirely clear how multiple agricultural practices such as tillage, biochar and different nutrient applications could influence corn physiology and yield. We conducted a three-year field experiment to study the responses of corn physiology, yield, and soil respiration to six different agricultural practices. The six treatments included conventional tillage (CT) or no tillage (NT), in combination… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
17
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 51 publications
1
17
0
Order By: Relevance
“…Pittelkow et al (2015) analysed the effect of tillage practices on crop yield, Yu et al (2016) explored the effect of different combinations of tillage practice and N fertilizer form on crop yield, Huang et al (2017) and Yanan et al (1997) considered the effect of manure versus inorganic N fertilizer application on nitrate leaching, and Huang et al (2015) analysed the effect of different tillage practices and N application rates on yield and N leaching. Furthermore, there are quite a few studies on the relation between rates of irrigation and N application and crop yield (Yin et al, 2014;Al-Kaisi and Yin, 2003;Rimski-Korsakov et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Pittelkow et al (2015) analysed the effect of tillage practices on crop yield, Yu et al (2016) explored the effect of different combinations of tillage practice and N fertilizer form on crop yield, Huang et al (2017) and Yanan et al (1997) considered the effect of manure versus inorganic N fertilizer application on nitrate leaching, and Huang et al (2015) analysed the effect of different tillage practices and N application rates on yield and N leaching. Furthermore, there are quite a few studies on the relation between rates of irrigation and N application and crop yield (Yin et al, 2014;Al-Kaisi and Yin, 2003;Rimski-Korsakov et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Studies suggest that tillage can influence plant physiology including increased rooting depth from decreased moisture in surface layers of tilled soil (Dwyer et al, 1996) or decreased mechanical resistance (Cox et al, 1990). Other studies indicate that tillage effects on plant physiology may interact with climate as Yu et al (2016) found that no-till likely increased yield during drought periods by conserving soil moisture. Since arable land represents more than 10% of the global land base (FAO, 2011), arable soils could provide a C sink to offset fossil fuel emissions (Paustian et al, 2016;Lal, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…A high N application rate will result in a high crop yield, but with high water pollution per hectare and per tonne of crop as well. The reason for the high water pollution per tonne of crop is that there is a threshold for the N application rate beyond which yield does not respond (Zhou et al, 2011), while the surplus N contributes to pollution (Carpenter et al, 1998;Vitousek et al, 2009). The form of N applied is another important factor affecting N losses.…”
Section: Introductionmentioning
confidence: 99%
“…Various studies show how increasing N application rates results in both increased crop yield and N leaching (Berenguer et al, 2009;Rong and Xuefeng, 2011;Valero et al, 2005;Zhou et al, 2011;Cooper et al, 2012;Good and Beatty, 2011). Pittelkow et al (2015) analysed the effect of tillage practices on crop yield, Yu et al (2016) explored the effect of different combinations of tillage practice and N fertilizer form on crop yield, Huang et al (2017) and Yanan et al (1997) considered the effect of manure versus inorganic N fertilizer application on nitrate leaching, and Huang et al (2015) analysed the effect of different tillage practices and N application rates on yield and N leaching.…”
Section: Introductionmentioning
confidence: 99%